Low-Dose Radiation and Genotoxic Chemicals Can Protect against Stochastic Biological Effects - Bobby R. Scott; Dale M. Walker; Vernon E. Walker (SAGE Publishing, 2004)
A protective apoptosis-mediated (PAM) process that is turned on in mammalian cells by low-dose photon (X and γ) radiation and appears to also be turned on by the genotoxic chemical ethylene oxide is discussed. Because of the PAM process, exposure to low-dose photon radiation (and possibly also some genotoxic chemicals) can lead to a reduction in the risk of stochastic effects such as problematic mutations, neoplastic transformation (an early step in cancer occurrence), and cancer. These findings indicate a need to revise the current low-dose risk assessment paradigm for which risk of cancer is presumed to increase linearly with dose (without a threshold) after exposure to any amount of a genotoxic agent such as ionizing radiation. These findings support a view seldom mentioned in the past, that cancer risk can actually decrease, rather than increase, after exposure to low doses of photon radiation and possibly some other genotoxic agents. The PAM process (a form of natural protection) may contribute substantially to cancer prevention in humans and other mammals. However, new research is needed to improve our understanding of the process. The new research could unlock novel strategies for optimizing cancer prevention and novel protocols for low-dose therapy for cancer. With low-dose cancer therapy, normal tissue could be spared from severe damage while possibly eliminating the cancer.